ANALISIS PENGENDALIAN PERSEDIAAN RAW MATERIAL SPARK PLUGS PADA PT DENSO INDONESIA JAKARTA TAHUN 2014 - Muhammad Zaini; Bagus Indrawan (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2016)
PT DENSO INDONESIA is a manufactured industry of vehicles spare parts. One of the products is spark plugs that contain insulator, housing, talk ring, ring form, gasket ring, nut lathe terminal, washer, and cup cutting. The questions formulated are how the company controlled the spark plugs productions, how the company arranged the economic order quantity / EOQ, safety stock, re-order point, maximum inventory, and total inventory cost, and how effective EOQ in controlling the company’s stock. The analysis method used in this study is EOQ. Based on the result, the EOQ set by the company was 12.560 units, the safety stock was 34.927 units, the spark plugs ordered 170 times in a year with 46.615 units of the stock, and maximum inventory was 47.487 units.